Peran Pendidikan Politik dalam Meningkatkan Kesadaran Hak dan Kewajiban Warga Negara - Kunradus Dappa Moda; Dorothea Novia Ludo Lubur; Samuel Rex Mulyadi Making; Timotius Woda Napu (Indo-MathEdu Intellectuals Journal, 2026)
Political education plays a crucial role in shaping citizens' awareness of their rights, obligations, and participation in a democratic society. This study aims to analyze the role of political education in raising citizen awareness and identify effective approaches to political education to support public political participation. The study employed a Systematic Literature Review (SLR) method for reviewing scientific articles published between 2015 and 2025. The review process involved identification, screening, eligibility assessment, and article selection based on established inclusion and exclusion criteria. Literature meeting the criteria was then analyzed using thematic analysis to identify patterns, themes, and trends in the research findings. The study's findings indicate that political education conducted in a critical, participatory, and contextual manner can enhance political understanding, awareness of citizens' rights and obligations, and public participation in the democratic process. Conversely, a one-way and doctrinal approach tends to result in limited political understanding. The findings also indicate that quality political education contributes to strengthening democratic culture at both the local and national levels. Therefore, strengthening political education through formal and non-formal education needs to be a priority in developing civic education policies.